2021
DOI: 10.3390/biomedicines9101365
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Functional Limitations, Gait Impairments, and Muscle Pathology in Alzheimer’s Disease: Studies in the 3xTg-AD Mice

Abstract: Gait impairments in Alzheimer’s disease (AD) result from structural and functional deficiencies that generate limitations in the performance of activities and restrictions in individual’s biopsychosocial participation. In a translational way, we have used the conceptual framework proposed by the International Classification of Disability and Health Functioning (ICF) to classify and describe the functioning and disability on gait and exploratory activity in the 3xTg-AD animal model. We developed a behavioral ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 73 publications
3
22
1
Order By: Relevance
“…A few biochemical and metabolic deficiencies have previously been reported in skeletal muscle in 3, 6, and 12 months old 3xTgAD male mice, including impaired mitochondrial function and decreased enzymatic activities of antioxidant enzymes and reduced activity of acetylcholinesterase ( Oddo et al, 2003a ; Monteiro-Cardoso et al, 2015 ). Additionally, a recent study using the 3xTgAD mouse model reported gait impairments and loss of mobility, along with markers of muscle pathology, such as lower endurance, and smaller grip strength ( Castillo-Mariqueo et al, 2021 ). However, the pattern of muscle atrophy and weakness and the functional changes related to NMJs and nerve-induced muscle force generation in 3xTgAD mice remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A few biochemical and metabolic deficiencies have previously been reported in skeletal muscle in 3, 6, and 12 months old 3xTgAD male mice, including impaired mitochondrial function and decreased enzymatic activities of antioxidant enzymes and reduced activity of acetylcholinesterase ( Oddo et al, 2003a ; Monteiro-Cardoso et al, 2015 ). Additionally, a recent study using the 3xTgAD mouse model reported gait impairments and loss of mobility, along with markers of muscle pathology, such as lower endurance, and smaller grip strength ( Castillo-Mariqueo et al, 2021 ). However, the pattern of muscle atrophy and weakness and the functional changes related to NMJs and nerve-induced muscle force generation in 3xTgAD mice remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical translational animal studies play a major role in neuroscience research to understand the roles of neuropeptides, neurohormones, and endogenous biomolecules in the normal function of human life such as cognition, emotion, and social interaction, and in pathological alterations developing into neurological and psychiatric disorders [82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97]. Various bioactive molecules are synthesized in the Try-KYN metabolic system.…”
Section: Discussionmentioning
confidence: 99%
“…In older adults, MNCDs are the primary cause of loss of autonomy, i.e., the ability to govern oneself, while balance and gait disorders are a major factor in loss of independence, and falls are the most common cause of accidental death. Moreover, cognitive troubles in older adults with MNCDs, especially AD, are often associated with motor disorders, including bradykinesia, rigidity, and balance and gait disorders [ 4 , 5 ], which increases the risk of falls [ 1 ]. The increased risk is explained by the impaired judgment (including the ability to assess environmental risks), memory and/or praxis and/or attention disorders (especially in a multitasking situation with poor integration of simultaneous stimuli), and damage to the nerve centers governing balance and gait that occur in individuals with MNCDs [ 6 , 7 ].…”
mentioning
confidence: 99%
“…There is also the negative impact of sarcopenia on motor skills, especially in older adults with MNCD. Indeed, a close link has been confirmed between sarcopenia and MNCDs, in particular AD [ 5 ]. Several previous studies have shown associations between slowing gait speed and cognition, suggesting that slow gait speed precedes cognitive decline by several years in people who will develop MNCD [ 5 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation